On lethargics and phrenetics: Descartes on the diseases of the mind - García Rodríguez, Sergio (Anales del Seminario de Historia de la Filosofía, 2022)
This paper reconstructs the explanation that Descartes offers about two diseases of the mind known in the seventeenth century: phrenitis and lethargy. For this aim, it is exposed, in the first place, how the Cartesian theory of mental representations give an account of the delusions and perceptual hallucinations of the madmen. Thus, Descartes's analysis of phrenitis and lethargy is presented, delving into the Cartesian theory of memory.
Keywords: Descartes; phrenitis; humours; lethargy; mechanicism; memory; mental illness; representationalism